Comparison of fragment analysis and PCR electrophoresis methods for the detection of FLT3‑ITD mutations in patients with acute myeloid leukemia - I. E. Maslyukova; D. V. Kurochkin; E. V. Martynova; V. I. Bakhtina; T. N. Subbotina (Онкогематология)
Background. The presence of the FLT3-ITD mutations in patients with AML serves as a marker of poor prognosis, which is included in the ELN 2017 risk stratification guideline. The main criterion for dividing patients into groups according to the predicted outcomes was the allelic ratio (AR) with a cutoff of 0.5: an AR value <0.5 is considered low, and ≥0.5 is considered high. At the same time, if the importance of AR determination is beyond doubt, the value of information about the length of the repeat and localization is still controversial. There are two common approaches for FLT3-ITD screening. The first, more accessible and cheaper method is the method of pCR electrophoresis and the second, more expensive and requiring special equipment, is the fragment analysis method, which allows not only to detect a mutation and determine the repeat length, but also to quantify or calculate AR.Aim. To compare fragment analysis and pCR electrophoresis in the search for the FLT3-ITD mutations in dNA samples from AML patients.Materials and methods. for the period of 2020–2022 fragment analysis and pCR electrophoresis were used to analyze blood and/or bone marrow samples taken from 45 patients with a confirmed diagnosis of AML who were treated at the Regional Clinical Hospital (Krasnoyarsk). Confirmation and identification of the FLT3-ITD mutations was performed by means of Sanger sequencing.Results. both methods revealed the FLT3-ITD mutations in 11 (24.45 %) patients among the 45 patients studied. According to the results of fragment analysis, the median repeat length was 42.70 base pairs (range 26.01–99.84 base pairs), AR was 0.532 (0.027–3.328), and the allelic frequency (Af) was 34.71 (2.67–76.90) %. Three different ITds were identified in one sample. Sanger sequencing identified mutations in 9 of 11 patients.Conclusion. fragment analysis and pCR electrophoresis showed similar results when analyzing samples with different ITd lengths and with different allelic ratios. but it can be assumed that in the case of a small ITd and low AR and Af values, when using pCR electrophoresis, the mutant allele will not be visualized, which can lead to a false negative result. The disadvantage of using the pCR electrophoresis method is also that without the use of special programs that allow determining the size and intensity of the band corresponding to the mutant allele, it is impossible to determine the AR value, which is important for AML risk stratification. Thus, for detection of the FLT3-ITD we recommend using the fragment analysis method.